The Dispersion Hypothesis in Macroeconomics - Sheffrin, Steven M. (The Review of Economics and Statistics, 1984)
Macroeconomics has always rested on the fiction that the behavior of aggregates was stable and, therefore, individual market phenomena could be safely ignored. In an important recent contribution, David M. Lilien challenged this fiction and argued that a large component of fluctuations in unemployment could be explained by the dispersion of employment growth across industries. This paper develops models of consumption and investment paper in which the dispersion of economic activity can play a role. The econometric evidence suggests an important role for the dispersion of economic activity in explaining aggregate consumption and investment.